Principles of orthopedic infection management. - KATES, STEPHEN L. (THIEME, 2017)
The medical world continues to make extraordinary advances in both scientific knowledge and surgical skill, yet despite these achievements, surgeons continue to struggle with the challenge of postoperative infection. Without proper prevention or treatment, orthopedic infection can become just as life-threatening as the initial trauma. This highly informative clinical go-to text provides the core principles, treatment options, and the latest information and research specifically for the purpose of helping physicians manage orthopedic infections and related issues. The book's key features includ.